(untitled) (Bangladesh Journal of Botany, 2019)
The cultivation of spices and nuts in different parts of the world characterized by high humidity and warm climate provides optimum conditions for the development of microorganisms, including the undesirable ones. To identify the microbial risk factor associated with dried spices and nuts samples available in local markets of Bangladesh, samples were collected and analyzed through standard microbiological procedure. In all the spices and nuts samples, the total aerobic heterotrophic bacterial (TAHB) level was below the standard unacceptable range (>106 CFU/g). Both Gram positive and Gram negative pathogenic bacteria viz., Staphylococcus aureus, S. epidermidis, Bacillus sp. and Enterobacter sp. were isolated from samples through screening staining properties, genus and group specific characters on selective and differential media along with morphological and biochemical tests. It could be assumed that dried spices and nuts might be the carrier of these types of pathogenic bacteria in foods when cooked using these ingredients and causes food borne illness.